2008
DOI: 10.1002/cncr.23215
|View full text |Cite
|
Sign up to set email alerts
|

Renin‐angiotensin system inhibitors, angiotensin I‐converting enzyme gene insertion/deletion polymorphism, and cancer

Abstract: BACKGROUND. Angiotensin I‐converting enzyme (ACE) inhibitors, angiotensin II antagonists, and the ACE insertion/deletion (I/D) gene polymorphism all influence serum angiotensin II action. Because angiotensin II levels have been associated with cancer, the objective of the current epidemiologic study was to investigate whether renin‐angiotensin system inhibitors and/or ACE genotypes were associated with an altered risk of colorectal, lung, breast, and prostate cancer. METHODS. Data were obtained from the Rotter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 33 publications
5
86
1
9
Order By: Relevance
“…RAS-inhibiting drugs seemed to protect against cancer in individuals with the DD genotype, which was associated with high levels of ACE. 59 Breast cancer An epidemiological study conducted in Chinese women in Singapore observed lower breast-cancer incidence in users of ACE inhibitors relative to nonusers with comparable cardiovascular conditions, 60,61 consistent with experimental data implicating ACE and Ang II in breast cancer.…”
Section: Clinical Observationssupporting
confidence: 55%
“…RAS-inhibiting drugs seemed to protect against cancer in individuals with the DD genotype, which was associated with high levels of ACE. 59 Breast cancer An epidemiological study conducted in Chinese women in Singapore observed lower breast-cancer incidence in users of ACE inhibitors relative to nonusers with comparable cardiovascular conditions, 60,61 consistent with experimental data implicating ACE and Ang II in breast cancer.…”
Section: Clinical Observationssupporting
confidence: 55%
“…The authors observed a dose-dependent, protective association between RAS inhibitor use and cancer risk in individuals with the ACE DD genotype (HR, 0.28; 95% confidence interval (CI), 0.10-0.79), while short-term, high-dose users were at risk for colorectal cancer progression in the II/ID stratum (HR, 3.83; 95% CI, 1.67-8.79). 41 On the other hand, in a meta-analysis reported by Sipahi et al with 61,590 patients enrolled in five trials with an ARB randomly given in at least one group, a modest risk to develop cancer was found in the ARB-receiving group (7.2% vs 6.0%, relative risk (RR) 1.08, 95% CI 1.01-1.15; p = 0.016). The clinical relevance of an RR of 1.08 needs to be further evaluated in trials with the development of malignancy as a primary outcome measure.…”
Section: Ras Blockers and Cancermentioning
confidence: 96%
“…They found that carriers of the high-activity genotype DD had an increased risk of breast cancer compared with low-activity II/ID genotype, but DD carriers who were exposed to long-term and high-dose medication were at a lower risk for other types of cancer. 41 All these results suggest that pre-clinical and clinical studies suggested that the blockade of the renin-angiotensin pathway with angiotensin system inhibitors might inhibit tumour growth in several cancer types. 35 …”
Section: Ras Blockers and Cancermentioning
confidence: 97%
“…A beneficial effect was also found when the analysis was limited to the 11 studies with long-term follow-up (RR 0.89, 95% CI 0.83-0.96). 4,6,13,15,18,[22][23][24]27,31,33 When the analyses were restricted to studies that investigated the effect of only ACE inhibitors on cancer risk, the 12 cohort and nested case-control studies showed a nonsignificant protective effect (RR 0.93, 95% CI 0.86-1.01), 4,12,15,16,19,21,23,29−33 and the 8 studies with longterm follow-up showed a significant protective effect (RR 0.89, 95% CI 0.80-0.98). 4,13,15,18,22,23,31,33 No significant change was observed when we excluded two studies with crude estimates.…”
Section: Effect Of Medication Use On Risk Of Cancermentioning
confidence: 99%